Trends in Research Focused on Hydrogen Production Based on the Web of Science - Gomez, Juan Marquez; Chamorro, Marley Vanegas; Caceres, Daniel Mendoza (International Journal of Energy Economics and Policy, 2022)
In the present research, a bibliometric analysis is performed on the trends of research focused on hydrogen production. The analysis was performed through an electronic search of the Web of Science database for publications between the years 2010 - 2019. HistCite software was used for the bibliometric analysis and VOSviewer software was used to create correlation graphs. The results obtained show that the number of publications has increased exponentially during the period 2010 - 2019. The research focused on hydrogen production is mainly driven by developed countries, of which China, the United States, and South Korea stand out. The predominant topics are focused on fuel energy (16.9%), electrochemistry (9.6%), and multidisciplinary materials science (8.69%). The most common keywords found in the analysis are "performance", "water", "generation" and "nanoparticles".